Packing boxes of Sunsweet prunes. - Gordon, John C. (photographer):::Creator::::::::::::
On the left in the background, women weigh and pack boxes of Sunsweet prunes. These boxes are then sealed on a mechanized belt, at which point a woman packs the boxes into crates.